The response of serum adipolin levels and insulin resistance index to high-intensity interval training in overweight men. - Rezaeimanesh, Davar (Revista Latinoamericana de Hipertensión, 2023)
Background: Adipolin is mainly expressed and synthesized from fat tissue, and with its anti-inflammatory properties, while improving insulin sensitivity, it also plays a role in reducing blood glucose levels. Therefore, in this study, the response of serum adipolin levels and insulin resistance index to High-Intensity Interval Training in Overweight Men was investigated. Materials and Methods: 24 overweight men (body mass index more than 25 kg/m2) were voluntarily selected and randomly divided into two groups of experimental (n=12) and control (n=12). The experimental group participated in 8 weeks of high intensity interval training (HIIT) via three sessions per week. Before and after intervention, blood sampling was performed to measure the serum levels of Adipolin, insulin, and fasting glucose. To analyze the data, independent t-test at the level of P<0.05 was used. Results: The comparison between the groups indicated that the values of adipolin and insulin resistance index significant improvement in the post-test of the experimental group compared to the control group (P>0.05). Based on the results of the intra-group test, the performance of high intensity interval training causing a significant increase in adipoline and a significant decrease in glucose, insulin and insulin resistance index in the experimental group. Conclusion: It seems that the implementation of high intensity interval training can have a major contribution to weight loss in overweight people by increasing adipoline and reducing the index of insulin resistance.